A Correlational Study of Home Environment and Adjustment With Reference to Adolescence Students - Singh, Amitesh Kumar; Singh, Namrata (Voices of Teachers and Teacher Educators, 2020)
The present study was conducted to assess the correlation between home environment and adjustment of adolescent students of Raipur City. A sample of 120 students, age group between 13-18 years had been taken from randomly selected schools, out of which 8 secondary schools. The sample was collected by using simple random sampling technique. Descriptive survey method was used to collect data. The tools used for this study were (1) Home Environment Scale developed by A. Akhtar and S. B. Saxena (2011) and (2) Adjustment Inventory developed by A K Singh and A. Sen Gupta. After the data analysis and interpretation it is concluded that, there were found a good correlation between adjustment problems on all dimension of home environment.